2008
DOI: 10.1016/j.juro.2008.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncological and Overall Outcomes of Percutaneous Radio Frequency Ablation in High Risk Surgical Patients With a Solitary Small Renal Mass

Abstract: In patients who have limited life expectancy or are high risk surgical candidates radio frequency ablation provides reasonable long-term oncological control and it may have a role in the management of small renal masses. Meticulous long-term followup is required in patients receiving radio frequency ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(87 citation statements)
references
References 20 publications
4
79
1
3
Order By: Relevance
“…Although long-term data are not yet available with these modalities, intermediate-term data demonstrates favorable recurrence and progression free survival. 11,12,13,14 The role of AS in the treatment of small RCN is well known and is considered a recommendation for elderly patient and in patients that are considered to be at high surgical risk. AS can be considered an option for healthy patients who have been informed of all treatment options and who insist on avoiding surgical extirpation or ablation.…”
Section: Review Of Management Options For the Ct1 Renal Massmentioning
confidence: 99%
See 2 more Smart Citations
“…Although long-term data are not yet available with these modalities, intermediate-term data demonstrates favorable recurrence and progression free survival. 11,12,13,14 The role of AS in the treatment of small RCN is well known and is considered a recommendation for elderly patient and in patients that are considered to be at high surgical risk. AS can be considered an option for healthy patients who have been informed of all treatment options and who insist on avoiding surgical extirpation or ablation.…”
Section: Review Of Management Options For the Ct1 Renal Massmentioning
confidence: 99%
“…Several series on AS have supported these findings and in general, the consensus is that ITS is not a predictive factor for an increase in GR or malignant potential in renal masses <4cm. 14,[18][19][20][21] Tumor growth rates in large single institution series and meta-analyses have been shown to be reasonably low (0.28-0.34cm/year) for most tumors. 6,7 Kunkle and co-workers concluded that there was no difference in the incidence of malignancy between tumors with zero growth versus those that do grow.…”
Section: Active Surveillance: How To Decidementioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence-free survival rate was 90.3 % in a study that followed up SRMs in single kidneys treated with RFA for over 40 months [36]. Stern et al published in their study disease-specific survival following RFA in T1a lesions of 93.4 % with a mean followup of 30 months.…”
Section: Oncological Outcome Of Rfamentioning
confidence: 99%
“…In a study that followed up SRMs in single kidneys treated with RFA for over 40 months [32], the recurrence free survival rate was 90.3%. Disease specific survival rate following RFA in T1a lesions was reported as 93.4% by Stern et al [33] in their study with a mean follow up of 30 months.…”
Section: Oncological Outcome Of Rfamentioning
confidence: 99%